(untitled) (Research, Society and Development, 2021)
The scarlet jade vines (Mucuna bennettii F. Muell, Fabaceae) is an exotic plant easily found in Federal District, Brazil, used as ornamentation in the region. This work aims to report the occurrence of the scale insect Coccus hesperidum L. (Hemiptera: Coccidae) on M. bennettii. Samples were collected from two scarlet jade vines located in Federal District and sent for identification. Infestations of this coccid were observed on leaves, stems, and trunks. Based on this report, the hots list of this polyphagous and cosmopolitan insect is expanded. In addition, C. hesperidum is reported the first time in Federal District, Brazil.